Diagnostic and therapeutic cholangioscopy in biliary diseases: a prospective study in Peru - Sanchez Cerna, Victor (2018)
Introduction: Cholangioscopy is a test that allows the evaluation of the biliary epithelium. It is used for diagnosis and management of biliary diseases. Objectives: Determine the success rate of complete removal of difficult stones with the use of laser lithotripsy through cholangioscopy as well as its complications. Determine the visual impression accuracy of bile duct injuries. Materials and methods: This is a prospective and descriptive study. We included 39 patients between July 2016 and July 2017 with diagnosis of difficult stones in the biliary tract and indeterminate stenosis of the biliary tract that were submitted to cholangioscopy. Results: Success rate of complete removal of difficult stones was 65.3%, there was one complication. Two laser sessions were required in 4 of the 17 patients who obtained complete removal of the stones. The visual impression accuracy of lesions in the bile duct to determine malignancy coincided in all cases with the final diagnosis of the patient. Conclusions: Laser lithotripsy allows a safe and effective treatment of the difficult stones of the bile duct. Precession of visual impression of lesions in the bile duct is very high.